Strategy Green Human Resource Management And Green Transformational Leadership Towards Environmental Performance Through Green Innovation - Ahmad Faisal; Indah Lestari; Ahmad (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to examine the influence of Green Human Resource Management (GHRM) and Green Transformational Leadership (GTL) on Environmental Performance (EP) with Green Innovation (GI) as an intervening variable on employees of the Environmental Service of Lebak Regency, Banten Province. The study applies a quantitative approach with an explanatory research method and uses the Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis technique. The number of samples in this study was 121 respondents selected through probability sampling techniques with a simple random sampling method. The results show that GHRM, GTL, and GI have a positive and significant influence on Environmental Performance. In addition, GHRM and GTL are also proven to have a positive and significant influence on Green Innovation. However, Green Innovation has not been able to significantly mediate the relationship between GHRM and GTL on Environmental Performance. These findings indicate that improving organizational environmental performance is more optimally achieved through direct strengthening of GHRM practices and the implementation of green transformational leadership rather than through green innovation as an intermediary variable. This research is expected to contribute to the development of sustainability management studies, especially in the public sector, as well as serve as a reference for organizations in developing strategies to improve sustainable environmental performance.